A DATA ENVELOPMENT ANALYSIS APPROACH FOR MEASURING THE EFFICIENCY OF EMPLOYEES: A CASE STUDY - Shirouyehzad, Hadi; Hosseinzadeh Lotfi, F.; Aryanezhad, Mir. B.; Dabestani, Reza (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Human resource management has become ever more important to organisational success. Many organisations have therefore realised that human resource management and performance can provide competitive advantage. The purpose of this study is to introduce a practical model for assessing employees